1981
DOI: 10.1002/cber.19811140532
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3‐Cyclohexantrion/2,6‐Dihydroxy‐2,5‐cyclohexadien‐1‐on Isomerisierung: Eine einfache Synthese für 2,6‐dioxysubstituierte 2,5‐Cyclohexadien‐1‐one

Abstract: Die bislang unbekannten 1,2,3-Cyclohexantrione 5 ksnnen in Form ihrer Chlorhydrine 2 oder deren Ester 4 leicht in die entsprechenden 2,6-Dihydroxy-2,5-cyclohexadien-l-one 6 oder deren Ester 8 umgelagert werden.l,2,3-Cyclohexanetrione/2,BDihydroxy-2,5cyclohexadien-l-one lsomerization:A Facile Synthesis of 2,BDioxy-substituted 2,5-Cyclohexadien-l-ones Hitherto unknown 1,2,3-~yclohexanetriones 5 masked as chlorohydrins 2 or as chlorohydrin esters 4 are easily rearranged yielding the corresponding 2,6-dihydroxy-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Similarly, Schank et al showed that the usual procedure of heating gem -chloroesters ( 181 ) in toluene, a useful preparative procedure for tricarbonyls (cf. section II.A.2), could not be applied to cyclohexanetriones.…”
Section: E Keto−enol Tautomerism (Scheme )mentioning
confidence: 99%
“…Similarly, Schank et al showed that the usual procedure of heating gem -chloroesters ( 181 ) in toluene, a useful preparative procedure for tricarbonyls (cf. section II.A.2), could not be applied to cyclohexanetriones.…”
Section: E Keto−enol Tautomerism (Scheme )mentioning
confidence: 99%
“…The pure aldol trichloroacetates were obtained at their corresponding boiling points. [6] Merger described only the synthesis of this compound, but its physical and spectroscopic properties are not described in the literature. Yield: 9.43 g, 63.5 %, colorless oil.…”
Section: General Procedures For the Synthesis Of Aldol Trichloroacetatesmentioning
confidence: 96%
“…The last step of the synthesis is in fact the substitution of the chlorine atom for various thiophenols under basic conditions, which leads to the final antiviral molecules. Also, Shank [6] obtained 3-chloro-4-hydroxy-1-oxaspiro [5.5]undec-3-en-2-one by chlorination of 4-hydroxy-1-oxaspiro [5.5]undec-3-en-2-one.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for vicdiketo esters 5 and vic-triketones 6, hydrate formation strongly dominates and these compounds are best stored in the hydrate form. In the case of an enolisable position next to the flanking carbonyl groups, enolisation (7 → 9) is facilitated 5 which can lead to self-condensation.…”
Section: Short Review Syn Thesismentioning
confidence: 99%